Neglected Foreign Body Aspiration Mimicking Lung Cancer Recurrence - Li L; Li MJ; Sun L; Jiang YL; Zhu J (Dove Medical Press, 2022)
Lei Li,1,* Meng-Jie Li,2,* Liu Sun,3,* Yuan-Liang Jiang,4 Jian Zhu5 1Department of the First Surgery, Wuhan Jin-Yin-Tan Hospital, Wuhan, 430011, People's Republic of China; 2Department of Respiratory Oncology, Renmin Hospital of Qingxian, Cangzhou, 062650, People's Republic of China; 3Department of Otolaryngology-Head and Neck Surgery, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China; 4Department of Radiology, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China; 5Department of Thoracic Cardiovascular Surgery, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhu; Yuan-Liang Jiang, General Hospital of Central Theater Command of the People's Liberation Army, 627#, Wuluo Road, Wuchangqu, Wuhan, Hubei, 430070, People's Republic of China, Tel +86-13871166489, Fax +86-27-50772388, Email zhujian0718@163.com; whzyyjyl@126.comAbstract: Foreign body aspiration (FBA) occurs less frequently in adults than in children. Case reports of FBAs occurring in adults after lung surgery are not found in the literature, and this particular condition is often misdiagnosed. We report a case in which the patient was diagnosed after various events. A 56-year-old female patient had undergone robotic-assisted resection of the right upper lobe. The patient recovered well after the operation, with a slight irritant dry cough. Chest computed tomography (CT) examination of the patient showed no obvious abnormality early postoperatively. However, she developed intermittent cough and hemoptysis at six months. Repeat chest CT showed a soft tissue shadow near the bronchus in the lower lobe of the right lung. Cancer recurrence, surgery-related foreign body residue, lymphoid reactive hyperplasia, or other reasons was considered. Further examination revealed a piece of watermelon seed shell blocking the bronchial opening of the lower lung. This case highlights the importance of medical history, careful physical examination and fiberoptic bronchoscopic examination after lung cancer surgery due to lung cancer recurrence risk or FBA.Keywords: foreign body aspiration, cancer recurrence, fiberoptic bronchoscopy, diagnosis